Aspek klinis dan tatalaksana gagal jantung pada anak: tinjauan pustaka - Herick Alvenus Willim; Cristianto Cristianto; Danayu Sanni Prahasti; Harie Cipta; Andi Anita Utami (Intisari Sains Medis, 2020)
Background: Heart failure in children is a serious health problem and associated with high morbidity and mortality. The causes and clinical manifestations of heart failure in children differ significantly with heart failure in adults. Therefore, a comprehensive understanding of heart failure in children is needed. This literature review aims to provide a review of clinical aspects and treatment of heart failure in children.Methods: This literature review included 47 relevant literature on clinical aspects, management of heart failure, and children. Different data sources or manual literature studies were used to search for articles related to literature topics.Results: The main causes of heart failure in children are congenital heart disease and cardiomyopathy. Diagnostic approach of heart failure in children is based on clinical features combined with supporting examination. The principal treatment of heart failure in children includes identification and elimination of precipitating factors, correction of underlying causes, and management of pulmonary or systemic congestion.Conclusion: Heart failure is a complex clinical syndrome that results from structural or functional disorders of the filling or ejection of blood from the ventricles of the heart where the clinical manifestations and management of heart failure in children are specific. Latar Belakang: Gagal jantung pada anak merupakan masalah kesehatan serius dan berhubungan dengan morbiditas dan mortalitas yang tinggi. Penyebab dan manifestasi klinis gagal jantung pada anak berbeda signifikan dengan gagal jantung pada orang dewasa. Oleh karena itu, dibutuhkan pemahaman komprehensif tentang gagal jantung pada anak. Tinjauan pustaka ini bertujuan untuk memberikan ulasan mengenai aspek klinis dan tatalaksana gagal jantung pada anak.Metode: Tinjauan pustaka ini melibatkan 47 literatur yang relevan tentang aspek klinis, tatalaksana gagal jantung, dan anak. Sumber data yang berbeda atau metode pencarian literatur manual digunakan untuk mencari artikel yang berkaitan dengan topik literatur.Results: Penyebab utama gagal jantung pada anak adalah penyakit jantung bawaan dan kardiomiopati. Pendekatan diagnosis gagal jantung pada anak berdasarkan gambaran klinis yang dikombinasikan dengan pemeriksaan penunjang. Prinsip tatalaksana gagal jantung pada anak meliputi identifikasi dan eliminasi faktor presipitasi, koreksi penyebab yang mendasari, serta penanganan kongesti pulmonal atau sistemik.Kesimpulan: Gagal jantung adalah suatu sindrom klinis kompleks yang terjadi akibat gangguan struktural atau fungsional dari pengisian atau ejeksi darah dari ventrikel jantung dimana manifestasi klinis dan tatalaksana gagal jantung pada anak bersifat khusus.